The effects of epidemics on capital markets volatility: A case study of Borsa Istanbul - Fatih Güzel; Melek Acar Boyacioğlu (CES Working Papers, 2021)
This study examines the effects of epidemics like H1N1, MERS and EBOLA on the volatility of capital markets through the case of Borsa Istanbul. The data set covers the period from 1/2/2009 - 8/11/2020 and consists of daily frequency observations. In the study, first, the appropriate volatility model for BIST 100 Index, which is the main market index of Borsa Istanbul, was determined. ARCH, GARCH, T-GARCH and E-GARCH models were tested to estimate the appropriate volatility model. According to the findings, E-GARCH (1,1) is more suitable for modelling the BIST 100 Index volatility. It was found that the H1N1 pandemic caused an increase in BIST 100 Index volatility, and negative news rather than positive news was effective on BIST 100 volatility. In addition, the effects of COVID-19 pandemic on BIST in the current situation were evaluated. During the pandemic period, the excessive increase in volatility and the negative trend in the return series are remarkable compared to previous periods.
Keywords: 330; H1N1; MERS; Ebola; COVID-19; Stock Market Volatility; Borsa Istanbul